Multi-properties optimization of welding parameters of wire arc additive manufacture in dissimilar joint of iron-based alloy and nickel-based superalloy using grey-based Taguchi method. (December 2021) - Xia, Yufeng; Peng, Mengxia; Teng, Haihao; Chen, Yanhong; Zhang, Xue
In order to adapt to the high temperature and heavy load process environment of large forgings, a novel die with "fist-like" structure was designed. The iron-based welding material (RMD248) as the "bone" layer and the nickel-based superalloy welding material (ERNiCr-3) as the "skin" layer were welded on the matrix by wire arc additive manufacture (WAAM). In this work, the grey based Taguchi methodology was used to optimize welding parameters (welding voltage, welding speed and wire feed speed) considering excellent multi-properties (hardness and ultimate tensile strength of high-temperature tensile test) of the dissimilar joint of RMD248 and ERNiCr-3. Further, analysis of variance was done to ascertain the influence of welding parameters on response parameters. Experimental results showed that welding speed was the most effective input parameter followed by wire feed speed and welding voltage. Finally, optimal result was verified through confirmation experiments. Meanwhile, the effect of welding speed on the microstructure and mechanical properties of joint was studied. The microstructures were characterized by optical microscopy (OM), energy dispersive spectrometer (EDS). The results indicated that the microstructure of RMD248 was consisted of more retained austenite at lower welding speed. For ERNiCr-3, the finer columnar crystal structure at higher welding speed was observed. At lower welding speed, the microhardness of RMD248 was just slightly lower, but that of ERNiCr-3 was significantly higher, and the ultimate tensile strength was higher. Therefore, the specimen at lower welding speed had better comprehensive mechanical properties.